2022
DOI: 10.35249/rche.48.2.22.24
|View full text |Cite
|
Sign up to set email alerts
|

Los escarabajos del estiércol (Coleoptera: Scarabaeidae: Scarabaeinae) de Quintana Roo, México: Lista anotada de especies y nuevos registros

Abstract: Los escarabajos del estiércol de la subfamilia Scarabaeinae suelen utilizarse como organismos focales para evaluar los impactos de origen antrópico sobre la biodiversidad. La distribución estatal de los Scarabaeinae en México es bastante heterogénea; mientras que algunos estados destacan por su alta diversidad, otros carecen de registros o la información disponible es escasa y se encuentra dispersa. La presente contribución constituye el primer intento de sintetizar toda la información disponible sobre la subf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…), C. femoralis (Chevrolat), and Onthophagus batesi Howden and Cartwright – are widely distributed in Neotropical forests (Capello and Halffter 2019; Sánchez-Hernández et al. 2022b) and are reported from diverse areas of Chiapas with different forest cover types (Sánchez-Hernández et al. 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), C. femoralis (Chevrolat), and Onthophagus batesi Howden and Cartwright – are widely distributed in Neotropical forests (Capello and Halffter 2019; Sánchez-Hernández et al. 2022b) and are reported from diverse areas of Chiapas with different forest cover types (Sánchez-Hernández et al. 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The three species identified as generalists -Canthon vazquezae (Martínez et al), C. femoralis (Chevrolat), and Onthophagus batesi Howden and Cartwrightare widely distributed in Neotropical forests (Capello and Halffter 2019;Sánchez-Hernández et al 2022b) and are reported from diverse areas of Chiapas with different forest cover types (Sánchez-Hernández et al 2020). For example, Canthon vazquezae appears to adapt to dominant habitat conditions due to its trophic breadth.…”
Section: Discussionmentioning
confidence: 99%